2017
DOI: 10.1080/20445911.2017.1322093
|View full text |Cite
|
Sign up to set email alerts
|

Painful semantic context modulates the relationship between action words and biological movement perception

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
(63 reference statements)
1
4
0
Order By: Relevance
“…The facilitated verb recognition in the first-person perspective fast action sentences compared with that in the first-person perspective slow action sentences seemed to be consistent with previous research which found that action simulation can be modulated by semantic context (e.g., Moody and Gennari, 2010 ; Bidet-Ildei et al, 2017a ; Sieksmeyer et al, 2021 ). One possible explanation for this might be that the fast action sentences were more semantically plausible and familiar than the slow action sentences.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The facilitated verb recognition in the first-person perspective fast action sentences compared with that in the first-person perspective slow action sentences seemed to be consistent with previous research which found that action simulation can be modulated by semantic context (e.g., Moody and Gennari, 2010 ; Bidet-Ildei et al, 2017a ; Sieksmeyer et al, 2021 ). One possible explanation for this might be that the fast action sentences were more semantically plausible and familiar than the slow action sentences.…”
Section: Resultssupporting
confidence: 90%
“…When the congruent action verbs were embedded in plausible sentences, the visual detection capacity and detection speed would be increased, which indicated that the plausibility of sentence context could modify the action simulation thus affecting the relationship between action verb and biological movements perception. Besides, Bidet-Ildei et al (2017a) asked participants to listen to an action sentence depicting either a painful or painless sentence (e.g., “The boy is sitting on a chair” vs. “The boy is sitting on a nail”) and then detect point-light biological movements. Results showed that movement detection was facilitated when the sentence depicted a congruent action but only in the painless context, which indicated that the painful context hindered the motor simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Future steps will be to enrich the functionalities using plug-ins and to develop the program for other operating systems. (Spencer et al, 2016) Children with autism (Kaiser et al, 2010) Adolescents with autism (Cusack, Williams, & Neri, 2015;Freitag et al, 2008) Adults with autism (Nackaerts et al, 2012) Adults with obsessive-compulsive disorder (Jung et al, 2009) Adults with schizophrenia (Kim, Doop, Blake, & Park, 2005) Horizontal mirror (Galazka et al, 2014) (Clarke et al, 2005) Masking PLD Scrambled mask (Bertenthal & Pinto, 1994;Bidet-Ildei et al, 2010;Bidet-Ildei, Gimenes, Toussaint, Almecija, & Badets, 2017;Bidet-Ildei, Gimenes, Toussaint, Beauprez, & Badets, 2017;Bidet-Ildei, Sparrow, & Coello, 2011;Chandrasekaran, Turner, Bülthoff, & Thornton, 2010;Cutting et al, 1988;Hiris, Humphrey, & Stout, 2005;Thornton et al, 1998; Adolescents born preterm presenting periventricular lesions (Pavlova et al, 2009;Pavlova, Staudt, Sokolov, Birbaumer, & Krageloh-Mann, 2003) In Young Adults (18 to 30 years)…”
Section: Discussionmentioning
confidence: 99%
“…To date, several questions remain under debate, such as the roles of local and global information (e.g., Bardi et al, 2011;Chang & Troje, 2009), the impact of motor and visual experience (see Bidet-Ildei, Orliaguet, & Coello, 2011, for a review) and the role of sex differences in perceptual performances (e.g., Pavlova, Sokolov, & Bidet-Ildei, 2015). Moreover, whereas links have been demonstrated between the processing of biological motion and the processing of language Bidet-Ildei, Gimenes, Toussaint, Beauprez, & Badets, 2017;Bidet-Ildei, Sparrow, & Coello, 2011;Bidet-Ildei & Toussaint, 2015;Pavlova et al, 2015), numbers (Badets et al, 2015) or social activities (Atkinson et al, 2004), the specificity of these links and their neural substrates remain open questions.…”
Section: Background and Motivationmentioning
confidence: 99%
“…To investigate this factor, several studies assessed the implication of action during action verb processing according to the semantic characteristics of the sentence in which the verb was included (Bidet-Ildei, Gimenes, Toussaint, Almecija, & Badets, 2017; Bidet-Ildei, Gimenes, Toussaint, Beauprez, & Badets, 2017;de Vega et al, 2014;Troyer et al, 2014). While some studies have clearly shown that semantics can affect peripheral motor reactions (i.e., grip force) to action verbs (Aravena et al, 2014(Aravena et al, , 2012, works focusing on the role of action representations show more varied conclusions.…”
Section: Language Characteristicsmentioning
confidence: 99%